Analysis of Raman, Mossbauer Spectra and Dielectric Behaviour of Sol-Gel Prepared Ni1-xCoxFe2O4 Spinel Ferrites. (1st August 2022) - Sowjanya, P.; Pavan Kumar, N.; Ganesh, K.; Ramana Reddy, M. V.
Abstract : Single-phase spinel ferrites with formula of Ni1−x Cox Fe2 O4 where x values are varying from 0 to 1 with 0.25 steps were synthesized by sol-gel technique. Microstructure, cation distribution, valence state of iron and dielectric properties have been discussed. From the deconvoluted Raman spectra the positions of five Raman modes and intensity variation was calculated. Cationic arrangement in A and B sites was estimated from deconvoluted Raman peaks. The characteristic magnetic patterns of ferrites were given by room temperature Mossbauer spectra. Parameters like isomer shift, hyperfine magnetic field, quadrupole shift were estimated for all ferrites after fitting Mossbauer spectra. From XPS (X-ray Photoelectron Spectroscopy) analysis +3 ionic state for iron was found. Dielectric parameters were also studied for ferrites at room temperature. NiFe2 O4 and Ni0.75 Co0.25 Fe2 O4 had high values of dielectric permittivity, AC conductivity and loss tangent. The ferrite Ni0.5 Co0.5 Fe2 O4 showed very less dielectric constant and conductivity values and dielectric loss resonance peak was around 1 kHz.